ANALISIS PENGARUH HARGA, SERQUAL DAN LOKASI TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Hotel Bangka Citr Pangkalpinang) - Munandar, Aris; Zamhari; Astuti, Nelly (Jurnal Progresif Manajemen Bisnis, 2018)
This is an undergraduate thesis that has been compiled by Aris Munandar with the student identification number: 230130075, was entitled in the Indonesian language "Analisis Pengaruh Harga, Serqual Dan Lokasi Terhadap Kepuasan Konsumen (Studi Kasus Pada Hotel Bangka Citr Pangkalpinang).. The purpose of this study is to examine the influence of Price, Servqual, and Location on Consumer Satisfaction at Bangka City Hotel Pangkalpinang. This research method uses Random sampling method. Research respondents are the Hotel Consumens of 95 95 people. Variables used are Price, Servqual and Location of independent variables and Consumer Satisfaction as independent variables developed according to its own indicators. This study uses Quantative analysis of primary data direct research results in the field. The results showed that: First, there is a significant influence of Price variables on Consumer Satisfaction. From the calculation results obtained value t_ (count) As big as 319 while t_ (table) with degrees free 93 on α (0.05) equal to 1.98580. Thus, t_ (count) (, 319)> t_ (table) (1.98580), so it is clear H_ (O) is rejected and H_ (1) received or from the calculation and processing data obtained value of sign equal to, 751. Second, there is a significant influence of Quality of Service variable on Consumer Satisfaction in Hotel Bangka City Pangkalpinang. From the calculation results, obtained value t_ (count) of 3.446 while t_ (table) with degrees free 93 on α (0.05) of 1.98580. Thus t_ (count) (1,98580)> t_ (table) (1,98580) so it is clear H_ (O) is rejected and H_ (1) received or from result calculation and data processing obtained sign value equal to, 000. Third, there is significant influence of Location variable on Consumer Satisfaction at Hotel Bangka City Pangkalpinang. From the calculation results obtained value t_ (count) of 3.167 while t_ (table) with degrees free 93 on α (0.05) of 1.98580. Thus, t_ (count) (1,98580)> t_ (table) (1,98580) so it is clear that H_ (O) is rejected and H_ (1) received or from the calculation result and data processing obtained by the sign value of 002. Fourth, there is significant influence of Price variable, Service Quality and Location together to Consumer Satisfaction at Hotel Bangka City Pangkalpinang. This is evidenced by the value F_ (count) of 1050866. While the critical value of F_ (table) with degrees of free numerator 3 and denominator 98 on α (0.05) of 2.70. Thus F_ (calculated) (1050866)> F_ (table) (2.70), so it is clear H_ (O) is rejected and accepted as well if using compare the sign value of 0,000. Based on the result of the research, the researcher conclude that Consumer Satisfaction at Bangka City Pangkalpinang Hotel can be improved through Price, Service Quality and Location.